Telling tales eaudiobook - Cleeves, Ann (Vera Stanhope, 2017)
"Demonstrating singular adeptness with mood and pacing, narrator Julia Franklin shines in this character-rich mystery set in northern England...Franklin's performance is direct and punchy, matching the speed and shrewdness of Vera's first-rate mind." — AudioFile Magazine From Ann Cleeves— New York Times bestselling and award-winning author of the Vera and Shetland series, both of which are hit TV shows—comes Telling Tales . "Ann Cleeves is one of my favorite mystery writers."—Louise Penny It has been ten years since Jeanie Long was charged with the murder of fifteen-year-old Abigail Mantel. Now residents of the East Yorkshire village of Elvet are disturbed to hear of new evidence proving Jeanie's innocence. Abigail's killer is still at large. For one young woman, Emma Bennett, the revelation brings back haunting memories of her vibrant best friend—and of that fearful winter's day when she had discovered her body lying cold in a ditch. As Inspector Vera Stanhope makes fresh enquiries on the peninsula and villagers are hauled back to a time they hoped to forget, tensions begin to mount. But are people afraid of the killer or of their own guilty pasts? With each person's story revisited, the Inspector begins to suspect that some deadly secrets are threatening to unfurl...